2019
DOI: 10.1080/09540105.2019.1705766
|View full text |Cite
|
Sign up to set email alerts
|

Peptides derived from fermented soybean meal suppresses intestinal inflammation and enhances epithelial barrier function in piglets

Abstract: This study was to investigate the effects of peptides derived from fermented soybean meal (FSP) on intestinal inflammation and epithelial barrier function of the piglets. Compared to fed soybean meal, piglets fed with fermented soybean meal (FSBM) exhibit lower serum levels of IL-6, IL-1β and D-lactate, and reduced ileum macrophage infiltration. Besides, the FSBM upregulated (p < 0.05) expression of mucins and tight junction (TJ) proteins in the jejunum and ileum of piglets. The FSP were prepared with alkali e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 44 publications
1
17
0
1
Order By: Relevance
“…TJ was a multi-protein complex composed of the claudin family, Occludin, junctional adhesion molecule, zonulin, and scaffold proteins ZO-1 (Vaarala, 2011). Among them, the claudin, Occludin and ZO-1 were associated with the intestinal barrier (Suzuki, 2013;Zhang et al, 2020). The early onset of autoimmune diabetes in BB-rats was associated with high gut permeability (Visser et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…TJ was a multi-protein complex composed of the claudin family, Occludin, junctional adhesion molecule, zonulin, and scaffold proteins ZO-1 (Vaarala, 2011). Among them, the claudin, Occludin and ZO-1 were associated with the intestinal barrier (Suzuki, 2013;Zhang et al, 2020). The early onset of autoimmune diabetes in BB-rats was associated with high gut permeability (Visser et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Fermented feeds were reported to enhance the intestinal barrier and immune function in poultry (79). Herein, improving the function of TJs may be attributed to the production of fermentation bioactive components such as oligosaccharides, isoflavones, and peptides, which protect intestinal cells and support their recovery (80). In addition to the presence of probiotic bacteria in fermented feed, TJ integrity and mucus secretion occurred in the gastrointestinal tract of broiler chicks.…”
Section: Figure 3 |mentioning
confidence: 99%
“…However, a variety of anti-nutritional factors (ANFs) present in SBM, such as antigenic proteins, trypsin inhibitors, and oligosaccharides, interfere with digestion and absorption and have negative effects on animal health [ 1 ]. Accumulating evidence has demonstrated that microbial fermentation improves the nutritional quality of SBM by reducing the content of ANFs and increasing nutrient bioavailability [ 2 , 3 , 4 ]. Fermented SBM (FSBM) is produced by the addition of fungal or bacterial microorganisms, including Lactobacillus plantarum , Bacillus subtilis , Aspergillus oryzae , and Neurospora crassa [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%